Hydrostatic Pressure and Built-In Electric Field Effects on the Donor Impurity States in Cylindrical Wurtzite GaN/AlxGa1−xN Quantum Rings - Guangxin Wang; Xiuzhi Duan; Rui Zhou (Advances in Condensed Matter Physics)
Within the framework of the effective mass approximation, the ground-state binding energy of a hydrogenic impurity is investigated in cylindrical wurtzite GaN/AlxGa1-xN strained quantum ring (QR) by means of a variational approach, considering the influence of the applied hydrostatic pressure along the QR growth direction and the strong built-in electric field (BEF) due to the piezoelectricity and spontaneous polarization. Numerical results show that the donor binding energy for a central impurity increases inchmeal firstly as the QR radial thickness (ΔR) decreases gradually and then begins to drop quickly. In addition, the donor binding energy is an increasing (a decreasing) function of the inner radius (height). It is also found that the donor binding energy increases almost linearly with the increment of the applied hydrostatic pressure. Moreover, we also found that impurity positions have an important influence on the donor binding energy. The physical reasons have been analyzed in detail.